Longitudinal observation of meticillin‐resistant Staphylococcus pseudintermedius pulsotypes in six veterinary hospitals in the north‐western United States. Issue 1 (2nd August 2022) - Perkins, Andrea V.; Sellon, Debra C.; Gay, John M.; Lofgren, Eric T.; Jones, Lisa P.; Davis, Margaret A.
Abstract: Background: Meticillin‐resistant Staphylococcus pseudintermedius (MRSP) infections in companion animals are increasing and are difficult to treat. Environmental contamination with MRSP in small animal primary care hospitals may pose an exposure risk to animal patients. Methods: This longitudinal study assessed the genotypic relationships of MRSP isolated from 39 environmental samples collected from six private small animal primary care hospitals, in the north‐eastern United States, between August 2018 and April 2019. Results: Of the 39 bacterial isolates, 18 unique pulsotypes were identified based on pulsed‐field gel electrophoresis, including six clusters of two or more indistinguishable isolates. Single pulsotypes were frequently detected from multiple hand‐contact and animal‐contact surfaces within a hospital during a single sampling event, but detection of a single pulsotype within the same hospital on subsequent visits was infrequent. However, one pulsotype was recovered from three separate hospitals, which suggests that either MRSP transmission between hospitals may have occurred via people, animals, or fomites or that there was a dominant community strain. Conclusions: Single strains of MRSP were isolated from various hand‐contact and animal‐contact surfaces within hospitals, indicating the important role of humans, animals and the environment in MRSP transmission. Additionally, the detection of a single strain between hospitals and over time suggests that either MRSP transmission between hospitals may have occurred via people, animals or fomites or that there was a dominant community strain.